Life cycle assessment of constructed wetlands for tertiary treatment of wastewater effluents in the cold-temperate zone - Jiang, Baiyang; Doh, Shu Ing; Suryati, Sulaiman; Abdul Syukor, Abd Razak (Engineered Science Publisher LLC, 2025)
This study performed a life cycle assessment on a constructed wetland designed for the treatment of municipal wastewater effluent in the Cold-Temperate Zone. The construction phase emerged as the primary driver of environmental impact, accounting for 71.99%. While the operational phase contributed substantially to Global Warming Potential. Two biomass utilization scenarios were proposed to enhance sustainability: animal feed (A), biofertilizer and biogas (B). Using the IMPACT 2002+ method, A performed worse than B in Human Health, Climate Change, and Resources, mitigating only 17%, 23%, and 83% of B’s impact reduction, respectively. In contrast, A outperformed B in Ecosystem Quality (1.5 times), while B was 10% more effective in reducing energy consumption under the CED method. These findings contribute to improved design and operation practices of constructed wetlands in cold-temperate regions that align with long-term ecological and resource conservation goals.